Comparison of porcelain veneer fracture in implant‐supported fixed full‐arch prostheses with a framework of either titanium, cobalt–chromium, or zirconia: An in vitro study. Issue 2 (21st March 2022) - Vahnström, Märta; Johansson, Petra H.; Svanborg, Per; Stenport, Victoria F.
Abstract: Objectives: The aim of this study was to compare porcelain veneer strength on screw‐retained implant‐supported fixed full‐arch prostheses with a framework of either milled titanium (Ti), cobalt–chromium (CoCr), and yttria‐stabilized zirconia (Y‐TZP) in an in vitro loading model. Materials and Methods: Fifteen screw‐retained maxillary implant‐supported full‐arch prostheses (FDP), five each of Ti, CoCr, and Y‐TZP frameworks with porcelain veneers were included. All FDPs were subjected to thermocycling before loading until fracture of the veneer. The load was applied at the distal fossa of the occlusal area of the pontic replacing 24. Fracture loads were analyzed, and the fracture quality was assessed. Statistical analysis on the fracture load was performed using Kruskal–Wallis test. The statistical significance was set at p  < .05. Results: There was no statistical significance found between the groups regarding fracture load. The highest and lowest load was seen within the CoCr FDP, varying between 340 and 1484 N. Different types of fracture appearances were seen. The Y‐TZP FDPs had a higher number of fractures locally in the loaded area while CoCr and Ti more often showed cracks in the anterior region, at a distance from the loaded area. Conclusions: Within the limitations of this study, the conclusion was that framework material may affect the fracture behavior of maxillary full‐arch bridges; however, there were no differences in veneer fracture strength when frameworks of Ti, CoCr, or Y‐TZP were compared.